Boosting pedagogical innovation in grammar class among EFL learners through microclass teaching strategies - Hesti Rokhaniyah; Alde Mulia Putra; Aries Fachriza (Studies in English Language and Education, 2025)
Microclass is a teaching strategy which involves dividing large classes into smaller, more manageable groups. These smaller classes are managed by learner facilitators who have received microteaching training and take on teacher-like responsibilities such as facilitating learner activities, assessing work, leading discussions, and providing feedback. This research was conducted at one of the Islamic universities in Ponorogo, Indonesia, employing an exploratory sequential research design with a triangulation method. Data was gathered through semi-structured interviews with eight learner facilitators, questionnaires from 32 learners, and classroom observations. Descriptive analysis was applied to evaluate the role of lecturers and learner facilitators, the level of involvement, and the impact of microclass on the English language teaching process. The finding shows that lecturers and learner facilitators worked together responsibly and effectively to implement microclass. Lecturers conducted microteaching sessions, observed the classes, consulted with learners, and provided feedback. Meanwhile, learner facilitators took on roles as motivators, collaborators, discussants, and initiators, employing techniques such as pairing and scaffolding throughout microclass stages. This collaborative approach resulted in a well-organized classroom. Additionally, the innovative microclass format significantly enhanced learner participation in the learning process, leading to the development of soft skills such as problem-solving, teamwork, and self-confidence. It enables language lecturers to engage learners while developing language and 21st-century soft skills, and it therefore merits further exploration.